Extending performance of concrete structures proceedings of the international seminar held at the University of Dundee, Scotland, UK on 7 September 1999 - Dhir, Ravindra K.; Tittle, Paul A. J. (Thomas Telford, 1999)
Topics discussed in 'Extending Performance of Concrete Structures' include developments in materials and methods for repair of existing structures and use in new construction. Themes of the seminar were materials, developments and practical applications.
Includes index.
Keywords: Concrete construction -- Congresses.; Reinforced concrete -- Congresses.; elektronické knihy; electronic books